Identifying Best Practices for WISEWOMAN Programs Using a Mixed-Methods Evaluation - Melanie Besculides, DrPH; Heather Zaveri; Rosanne Farris, PhD; Julie Will, PhD (Centers for Disease Control and Prevention, 2005)
IntroductionRecommendations on best practices typically are drawn from unique settings; these practices are challenging to implement in programs already in operation. We describe an evaluation that identifies best practices in implementing lifestyle interventions in the Center for Disease Control and Prevention's WISEWOMAN program and discuss our lessons learned in using the approach.MethodsWe used a mixed-methods evaluation that integrated quantitative and qualitative inquiry. Five state or tribal WISEWOMAN projects were included in the study. The projects were selected on the basis of availability of quantitative program performance data, which were used to identify two high-performing and one low-performing site within each project. We collected qualitative data through interviews, observation, and focus groups so we could understand the practices and strategies used to select and implement the interventions. Data were analyzed in a multistep process that included summarization, identification of themes and practices of interest, and application of an algorithm.ResultsPilot testing data collection methods allowed for critical revisions. Conducting preliminary interviews allowed for more in-depth interviews while on site. Observing the lifestyle intervention being administered was key to understanding the program. Conducting focus groups with participants helped to validate information from other sources and offered a more complete picture of the program.ConclusionUsing a mixed-methods evaluation minimized the weaknesses inherent in each method and improved the completeness and quality of data collected. A mixed-methods evaluation permits triangulation of data and is a promising strategy for identifying best practices.